Factors controlling the emissions of volatile organic acids from leaves of Quercus ilex L.(Holm oak) - Gabriel, R; Schafer, L; Gerlach, C (Atmospheric Environment, 1999)
Direct emissions and emission of precursor compounds of acetic and formic acid from higher plants are a signiÞcant source of these acids in the atmosphere. To travel from the plant cell to the atmosphere, a gas molecule must Þrst leave the liquid phase and then enter the internal leaf gas phase. The apoplast (cell wall) is the last barrier before the molecule can escape through the stomata. During Þeld experiments we monitored the gas exchange (H 2 O, CO 2 , organic acids) of Quercus ilex L. leaves. The exchange rates of acetic and formic acid under Þeld conditions followed a typical diurnal pattern and ranged between!10 (uptake) and 52 (emission) nmol m~2 leaf area min~1 with the maximum around noon. Growth chamber experiments indicate that the emission is related to the stomatal conductance. We discussed the exchange rate of organic acids between the cell wall and the atmosphere in connection with HenryÕs law, and the physicochemical conditions in the cell wall. The evaluation showed that for apoplastic pH values between 4 and 5, 26Ð130% of the measured acetic acid emission based on leaf area could be predicted. ( 1999 Elsevier Science Ltd. All rights reserved.
Keywords: aba abscisic acid; Gas exchange; organic acids; Quercus ilex

Simultaneous field measurements of terpene and isoprene emissions from two dominant Mediterranean oak species in relation to a north American species - Kesselmeier, J; Bode, K; Schafer, L (Atmospheric Environment, 1998)
ÐWe investigated the emission of monoterpenes and isoprene from tree species growing at a site near Montpellier (South France). We compared the emission pattern and behaviour of two important oak species representative of the Mediterranean ecosystem, namely, Quercus ilex (Holm oak), a strong monoter- pene emitter, and Quercus pubescens (White oak), a strong isoprene emitter by measuring the two species growing side by side simultaneously. Additionally, we included a Californian oak species Quercus agrifolia (Coast Live Oak), which is anatomically and morphologically comparable with Quercus ilex. The data show that Live Oak and Holm oak though they appear identical, di¤er as far as the emission of terpenoids is concerned, emitting isoprene or terpenes, respectively. The isoprene emitting White oak and the monoter- pene emitting Holm oak react identically to the same environmental conditions, ßuctuating light and temperature, indicating that close metabolic pathways are involved in the actual emission of the C5 and C10 compounds from these two species, as seen under Þeld conditions. ( 1998 Elsevier Science Ltd. All rights reserved
Keywords: isoprene; Monoterpenes; oak; quercus agrifolia; Quercus ilex; Quercus pubescens; volatile biogenic hydrocarbons

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds